Local Influence on Bandwidth Estimation for Kernel Smoothing - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 2001)
Examines the problem of assessing local influence on the optimal bandwidth estimation in kernel smoothing based on cross validation. Role of the bandwidth for kernel smoothing in the model fitting; Applications of the proposed diagnostic; Discussion on the perturbation scheme.